Sweet tomorrows : a Rose Harbor novel - Macomber, Debbie (New York : Ballantine Books, an imprint of Random House, a division of Penguin Random House LLC, 2016)
Nine months ago, Mark Taylor abruptly left Cedar Cove on a perilous mission to right a wrong from his past. Though Mark finally confessed his love for her, innkeeper Jo Marie Rose is unsure if he's ever coming back.
Keywords: Hotelkeepers -- Fiction; Female friendship -- Fiction; Interpersonal relations -- Fiction; Love stories